ANALISIS SWOT PADA INDUSTRI JAGUNG MANIS DI KOTA PAYAKUMBUH (Studi Kasus : Jagung Manis F1aina) - Ningsih, Dea Gita; Sari, Lapeti; Setiawan, Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The success of Industrial and trading sector have given big contribution in creating national economic structure. One of food industries in Payakumbuh city that have vase growth is F1 Aina corn industry. This study aims to determine the strengths, weaknesses, opportunities and threats in the development of Sweet Corn Industry F1Aina. Knowing the industry development strategy F1Aina Sweet Corn. The analytical method used is the SWOT analysis (Strengths, Weaknesses, opportunites, Threats). This research was conducted in the District Payakumbuh West Payakumbuh Nagari Koto Nan IV. The population in this study is the sweet corn industry F1Aina located in Payakumbuh, Engineering sample selection of respondents was done by purposive (purposional sampling) that is as much data was collected by interview, observation, and questionnaires. Sampling method is purposive sampling. This type of data consists of primary and secondary data. The results of the SWOT analysis matrix values can be obtained from internal factors 17 and the value of the matrix of external factors 5. Application Aggressive Strategy / Strategies SO Sweet Corn Industry F1Aina means are in a situation that is very profitable or have the power and opportunity. The strategy should be applied is taking advantage of opportunities for profit. Based on the analysis of internal factors and external indicators of the strength of the sweet corn industry F1Aina in Payakumbuh is supervise the activities of production, production capacity is excellent.Keywords : Food Industry, SWOT Analysis, Development Strategy